Concomitant Anomalous Branching of Facial Nerve and Double Parotid Duct: A Case Report - Soliman, Amro Mohamed; Ramli, Elvy Suhana; Das, Srijit; Abd Ghafar, Norzana (IIUM Medical Journal Malaysia, 2017)
The facial nerve divides within the parotid gland into upper temporozygomatic and lower cervicofacial branches. The two branches further subdivide and emerge from the parotid gland as five main branches. We observed a rare anomalous branching pattern of the facial nerve along with double parotid duct on the right side of a 50-year-old male cadaver. The two parotid ducts emerged at the level of the anterior border of parotid gland then united to form one single duct thereby opened into the oral cavity. The first duct (D1) emerged from the upper one third of the anterior border of the parotid gland and traversed horizontally for 9 mm to join the second duct. Knowledge of anomalous branching pattern of facial nerve and double parotid ducts may be beneficial for maxillofacial surgeons.